PENGARUH KUALITAS AUDIT TERHADAP POTENSI RISIKO FRAUDULENT FINANCIAL STATEMETN MELAUI FRAUD SCORE MODEL - Cahyati, Ari Dewi; Nurjannah, Aris (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2014)
This study examined the effect of audit quality to the potential risk of fraudulent financial statementthrough fraud score models. The population in this study is all manufacture company listed on the Indonesia StockExchange. Using purposive sampling method was obtained for companies audited by KAP big four is 39 and asmuch as non big four is 30. This study uses secondary data manufacturing company in 2010-2012. audit qualitymeasured by the big four and non big four, risk of fraudulent financial statement is measured by the sum of accrualsquality and financial performance. Results of research quality audit negative effect on the potential risk of fraudulentfinancial statements. Empirical evidence shows that the mean and standard deviation of the group of companiesowned by service users KAP Non Big Four is greater than the service user company KAP Big Four. T his supportsthe second hypothesis which states that the level of risk of fraudulent financial statement on the company KAPservice users Non Big Four is greater than the service user company KAP Big Four.